شعرية العتبات النصية في النقد المعاصر - خذري, عالمة (جامعة الوادي - University of Eloued, 2017)
إن تطور الدراسات النقدية المعاصرة حول النص بدأت تنتقل من دراسة النص باعتباره خطابا أصليا إلى خطابات موازية له، يحركها في ذلك فعل التأويل وينشطها فعل القراءة شارحا ومفسرا شكل معناه، ولافتا النظر إلى الخصائص الفنية التي يتميز بها هذا الخطاب. وكنتيجة للتطورات الثقافية و النقدية الحاصلة على مستوى الفكر، أخذ النص الأدبي تمظهرات عدة تعكس رؤية الأديب والناقد للواقع وتتخذ ملامح الانفتاح على المطلق بدل التمركز على الذات فهي كتابة دون حدود تسعى إلى أن تتمثل كل شيء له علاقة بالنص الأصلي، فليس هناك أمور تحد أوتمنع فعل الكتابة، بل يصبح كل شيء عرضة للكتابة و المناقشة، أنها ثقافة اللامحدود، تحاول هذه الكتابة أن تنقل الدراسة من فلسفة النص الواحد إلى فلسفة المجاورات ( العتبات النصية ) وهي بذلك تعيد هندسة الكتابة النقدية بالاعتماد على بلاغة الفضاء النصي القائم على التعدد لا الوحدة، لذا فهو ينفتح على العتبات النصية مثل : العنوان، الهامش الإهداء،البداية، النهاية Poetic “Text Thresholds” in the Arab Contemporary Critical Thought. The evolution of contemporary critical studies of the text began to shift the focus from the study of the text as the original discourse to the parallel discourses that surround it. This has been driven by the act of interpretation and activated by the act of reading used for explaining its meaning form, yet pointing out the technical characteristics featured by this discourse. Because of cultural developments at the level of thought, the literary text is manifested in several forms, which reflected the vision of the writer as a critic of reality, and which took the features of openness to the absolute, rather than being limited to itself. This kind of writing is not restricted; it seeks to represent everything related to the original text. Therefore, nothing can limit or prohibit the act of writing, and everything can be subject to writing or discussion, whichis referred to as the culture of infinity. This writing attempts to turn the emphasis of the study from the text to the philosophy of the surroundings (text thresholds). Accordingly, it reformulates critical writing underpinning the eloquence of the textual space, which is based on diversity not
مقال
Keywords: شعرية؛ العتبات النصية ؛ النقد المعاصر